A molecular-scale study on the hydration of sulfuric acid-amide complexes and the atmospheric implication. (December 2018) - Ge, Pu; Luo, Gen; Luo, Yi; Huang, Wei; Xie, Hongbin; Chen, Jingwen
Abstract: Amides are ubiquitous in atmosphere. However, the role of amides in new particle formation (NPF) is poorly understood. Herein, the interaction of urea and formamide with sulfuric acid (SA) and up to four water (W) molecules has been studied at the M06-2X/6-311++G(3df, 3pd) level of theory. The structures and properties of (Formamide)(SA)(W)n (n = 0–4) and (Urea)(SA)(W)n (n = 0–4) clusters were investigated. Results show that the interaction of SA with the CO group of amides plays a more important role in amide clusters compared with the NH2 group. Proton transfer to water molecule become dominant in highly hydrated amide clusters at lower temperatures. There is no proton transfer to CO group in formamide clusters. The Rayleigh light scattering intensities of amide clusters are comparable to that of amine and oxalic acid clusters reported previously. Moreover, unhydrated (Amide)(SA) clusters have similar or even higher ability than hydrated SA clusters to participate in ion-induced nucleation. In comparison with formamide, urea has more interacting sites and its clusters have higher Rayleigh light scattering intensities, larger dipole moment, stronger interaction with SA and lower water affinity. The intermolecular interaction in (Formamide)(SA) is slightly weaker than that of SA dimer, which may be compensated by the high concentration of formamide, thus enabling formamide to participate in initial steps of NPF. This study may bring new insight into the role of amides in initial steps of NPF from molecular scale and could help better understand the properties of amide-containing organic aerosol. Graphical abstract: Highlights: No proton-transfer to CO group occurs in formamide clusters. High concentration of formamide compensates its unfavorable interaction with SA. Proton transfer to water is significant when highly hydrated at low temperature. Interaction between SA and CO group play important role in amide clusters. The amine substituent in amides affects the cluster structures and properties.